Associations of Lifestyle Factors With Cognition in Community-Dwelling Adults Aged 50 and Older: A Longitudinal Cohort Study - Huang, Zhezhou; Guo, Yanfei; Ruan, Ye; Sun, Shuangyuan; Lin, Tao; Ye, Jinghong; Li, Jun; He, Lihua; Wang, Sen; Shi, Yan; Wu, Fan (Frontiers in Aging Neuroscience, 2020)
In the absence of an effective treatment to alter the progressive course of cognitive decline and dementia, identification of modifiable risk factors that could promote healthy cognitive aging has become a public health research priority. This study seeks to comprehensively determine the contemporaneous associations of a broad spectrum of time-varying modifiable lifestyle factors with age-related cognitive decline in a large population-based cohort of older adults. A total of 5711 subjects aged 50 and older from the WHO Study on global AGEing and adult health (SAGE) in Shanghai were studied. Repeated measures of lifestyle factors and cognitive performance were conducted in 2009-2010 and 2014-2015. Linear random slope models were used to evaluate the contemporaneous associations between time-varying lifestyle factors and cognitive performance. Person-mean centering method was used to disaggregate the between- and within-person effects in the time-varying lifestyle factors in the random slope models. We found that higher vegetable and fruit consumption, as well as higher level of physical activity were positively associated with all cognitive domains. Body mass index (BMI) was negatively associated with all cognitive domains, whereas waist-to-hip ratio (WHR) was negatively associated with verbal fluency score only. Sedentary time was negatively associated with digit span score but positively associated with verbal fluency score. The between-person effects seem to be more dominant than within-person effects. Overall, our findings suggest better management of multiple lifestyle factors may protect against cognitive decline in later life. Higher vegetable and fruit consumption and physical activity are protective, whereas obesity is detrimental to cognitive decline in older adults. This study underpins the development of multi-domain lifestyle recommendations to promote healthy cognitive aging.